Redescription of Spinitectus tabascoensis (Nematoda: Cystidicolidae) from fishes of the Lacandon rain forest in Chiapas, southern Mexico, with remarks on Spinitectus macrospinosus and S. osorioi - Moravec, František; Salgado-Maldonado, Guillermo; Caspeta-Mandujano, Juan M; Gonzáles-Solís, David (Folia parasitologica, 2009)
Two little-known species of Spinitectus (Nematoda: Cystidicolidae) were, for the first time, recorded from fishes of the Lacantún River (Usumacinta River basin) in the Lacandon rain forest, Chiapas, southern Mexico: S. tabascoensis Moravec, García-Magana et Salgado-Maldonado, 2002 in intestines of Ictalurus furcatus (Valenciennes) (Ictaluridae) (adults and juveniles), Cathorops aguadulce (Meek) and Potamarius nelsoni (Evermann et Goldsborough) (both Ariidae) (in both only juveniles), and S. osorioi Choudhury et Pérez-Ponce de León, 2001 in Atherinella alvarezi (Díaz-Pardo) (Atherinopsidae) (adults in intestine) and Eugerres mexicanus (Steindachner) (Gerreidae) (adults and juveniles in stomach). Eugerres mexicanus, C. aguadulce and P. nelsoni represent new host records. Detailed light and electron microscopical studies of S. tabascoensis revealed some taxonomically important, previously not observed features, such as cuticular spines arranged in four sectors, the cephalic structure, the number (2) of ventral precloacal ridges or the structure of the male caudal end. Therefore, Spinitectus tabascoensis is redescribed. Spinitectus macrospinosus Choudhury et Perryman, 2003, described from ictalurids in Canada and the USA, is considered its junior synonym. Spinitectus tabascoensis seems to be a specific parasite of Ictalurus spp., whereas C. aguadulce and P. nelsoni, as well as some other fishes, serve only as its paratenic hosts. The definitive hosts of S. osorioi are atherinopsid fish (A. alvarezi, Chirostoma spp.), whereas the gerreid E. mexicanus probably serves only as its postcyclic host.
Keywords: financování organizované; Mexiko; Animals; Financing, Organized; Nematoda; Female; mužské pohlaví; zvířata; hlístice; Fishes; Male; Mexico; ženské pohlaví; ryby